The Effect of Self-Directed Learning Model on Critical Thinking Ability and Learning Independence in Geography Subjects - Nasywa Salsabila; Alfi Sahrina; Zubaidah Nur Aini (Universitas Negeri Gorontalo, 2025)
The problems in geography learning are difficulties in submitting and providing answers related to material and teacher-centered learning activities. This research aims to examine of the effect of the self-directed learning model on critical thinking skills and learning independence in geography subjects. This research is a quasi-experiment with a pretest-posttest control group design. Data collection methods include written test of essay questions about critical thinking skills and questionnaires regarding learning independence. The subjects of this study were class X-3 as the experimental class and class X-1 as the control class with a total of 34 students every class. Based on the results of Mann-Whitney U hypothesis testing, it is known that critical thinking ability has an Asymp. Sig 0.000 0.05. So, H0 is rejected and H1 is accepted, meaning that there is an effect of the self-directed learning model on critical thinking skills in geography subjects. Meanwhile, the learning independence shows the value of Asymp. Sig value of 0.000 0.05. then H0 is rejected and H1 is accepted, which means that there is an effect of the self-directed learning model on learning independence in geography subjects. The research findings show that the syntax of the self-directed learning model, namely implementation and evaluation as well as the syntax of identifying learner abilities and learning resources, affects critical thinking skills. Meanwhile, the syntax that affects learning independence is the syntax of identifying learner abilities and learning resources. Therefore, this research is expected to make a significant new contribution in understanding the self-directed learning model as an effort to improve critical thinking skills and learning independence in geography subjects.